Financial Distress And Debt To Asset Ratio Can Moderate Stock Price Problems - Sunaryo, Deni (CV. Inara, 2022)
This study aims to analyze the effect of Return On Equity, Total Asset Turn Over, and Cash Ratio on Stock Prices moderated by Financial Distress and Debt to Asset Ratio. This study uses the objects of the Property and Real Estate sub-sector companies on the Southeast Asian Stock Exchange for the period 2012-2020. The data collected is secondary data with the documentation method in the form of the company's annual report. The analytical tool used to test the hypothesis is SPSS 26. The sampling method used in this study using purposive sampling technique obtained 11 companies that present complete financial statements, so that obtained as many as 99 samples. The analytical technique used is descriptive statistical analysis, classical assumption test,MRA, multiple linear regression, t test, and f test. The result of the research partiallyconcludes that Return On Equity has no effect on Stock Price, Total Asset Turn Over has a significant effect on Stock Price, and Cash Ratio has a significant effect on Stock Price. The results of the study simultaneously Return On Equity, Total Asset Turn Over, and Cash Ratio significant effect on stock prices. MRA research results shows that Financial Distress Moderate Return On Equity on Stock Prices, Financial Distress moderate Total Asset Turn Over to Stock Price, Financial Distress does not moderate Cash Ratio to Stock Price, Debt To Asset Ratio moderates Return On Equity to Stock Price, Debt To Asset Ratio moderate Total Asset Turn Over to Stock Price, and Debt To Asset Ratio does not moderate Cash Ratio to the Share Price.